Use of the Agricultural Production Systems Simulator (APSIM) to assess the long-term impact of conservation agriculture on wheat-based systems in Tunisia - CGIAR Research Program on Wheat (2019)
peer-reviewed journal article showing potential value of adopting conservation agriculture practices in Tunisia.